Simulacra as a Distortion of the Meaning of the Mass for the Dead in the Music Video “Dalam Hitungan” by the Band.Feast - Pasya, Daffa Kamal; Nurliah , Nurliah; Dristiana Dwivayani, Kadek; Muhammad, Harry Isra (CV. Publikasi Indonesia, 2026)
This study examines simulacra as a form of distortion of the meaning of the ritual of the Soul Mass in the video clip